Ocorrência de Microcerella halli (Engel) (Diptera, Sarcophagidae) em uma Carcaça de Cobra no Sudeste Brasileiro - Moretti, Thiago de C. [UNESP]; Allegretti, Silmara M.; Mello-Patiu, Cátia A.; Tognolo, Alexandre M.; Ribeiro, Odair B.; Solis, Daniel R. [UNESP] (FapUNIFESP (SciELO), 2009)
The occurrence of 27 second-instar larvae of the flesh fly Microcerella halli (Engel, 1931) (Diptera, Sarcophagidae) in a carcass of a snake usually called as Urutu, Bothrops alternatus (Duméril, Bibron & Duméril, 1854) (Serpentes, Viperidae, Crotalinae) is reported. The snake was kept in captivity in a snake farm in Morungaba, São Paulo state, Brazil. Descriptions of reptile carcass colonization by insects and general biological data of this flesh fly are scarce and this necrophagic behavior is described for the first time in literature. © 2009 Sociedade Brasileira De Entomologia.
Occurrence of Microcerella halli (Engel) (Diptera, Sarcophagidae) in snake carrion in southeastern Brazil
Keywords: Flesh flies; Fly colonization; Forensic entomology; Reptile carcass